2020
DOI: 10.13106/jafeb.2020.vol7.no12.329
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Pressure and Business Performance in East Java Batik Industry

Abstract: This study aims to assess the impact of competitive pressure and innovation capability on business performance in small-and mediumsized enterprises (SMEs) in the batik industry in East Java, Indonesia. Furthermore, this study explores the impact of competitive pressure on business performance through innovation capability as a mediating variable. This research was quantitative using primary data with questionnaire as a method of sampling collection. The measurement of the variables was captured using Likert sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…The results from Study 1 and Study 2 reported an opposite and significant relationship between competitive pressure and firm performance. Study 1 presented that competitive pressure positively affects firm performance, which is in line with most past studies [ 21 , 108 , 109 ]. And, a few studies reported there is no significant relationship between competitive pressure and firm performance [ 110 ].…”
Section: Discussionsupporting
confidence: 88%
“…The results from Study 1 and Study 2 reported an opposite and significant relationship between competitive pressure and firm performance. Study 1 presented that competitive pressure positively affects firm performance, which is in line with most past studies [ 21 , 108 , 109 ]. And, a few studies reported there is no significant relationship between competitive pressure and firm performance [ 110 ].…”
Section: Discussionsupporting
confidence: 88%
“… Soewarno et al (2020) defined competitive pressure as the level of competitive atmosphere in the industry, and Alaskar et al (2021) defined competitive pressure as the pressure felt by the industry to remain competitive. In this study, competitive pressure is defined as the level of pressure felt by the textile industry from its peers to remain competitive, and the level of competitive atmosphere.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Soewarno et al (2020) defined competitive pressure as the level of competitive atmosphere in the industry, andAlaskar et al (…”
mentioning
confidence: 99%
“…Competition pressure is the level of competition in the business sector (Soewarno et al, 2020). According to Bernard et al (2006), competitive pressure arises when companies compete with competitors on the commodities market through frequent competitive interactions with other firms seeking to win customers, raise market shares, or struggle for survival.…”
Section: Competitive Pressurementioning
confidence: 99%
“…Additionally, Soewarno et al (2020) reported that when there is a high degree of consumer demand, companies are more likely to pursue creativity, than when there is a low level of competition, resulting in higher transformative adoption. Turner and Endres (2017) advised that entrepreneurs must continue their survival efforts in the face of environmental change and competitive pressure because competition pushes entrepreneurs to think more creatively to outperform their rivals, resulting in revolutionary creativity.…”
Section: Competitive Pressurementioning
confidence: 99%